THE RELATIONSHIP BETWEEN MENTAL WORKLOAD AND WORK STRESS IN TEACHERS OF SCHOOLS OF DISABLED CHILDREN - Tsimaratut Tahrirah (Universitas Airlangga, 2019)
A profession as a teacher of schools of disabled children (SLB) is one of the jobs that can cause work stress. Teachers at SLB need more patience, attention, and special skills than teachers in ordinary schools. The purpose of this study was to determine the relationship between mental workload and work stress on SLB teachers in Jombang. This study was an analytical observational study with a cross sectional design. The samples in this study were three out of nine SLBs in Jombang that were chosen through random sampling. The data collection was done by using a questionnaire filled by 33 respondents. The questionnaire included the Subjective Workload Assessment Technique (SWAT) questionnaire to measure mental workload, and The National Union of Teacher (NUT) Stress Survey to measure work stress on SLB teachers in Jombang. The results showed that there was a strong relationship between mental workload and work stress (p-value = 0.049 and r = 0.360). In conclusion, most SLB teachers in Jombang are female and are in the age group of young adults. The Background Education of SLB teachers mostly comes from non-Special Education (PLB) department and the majority of them were new and had been teaching for years. According to the result of this study, the mental workload of SLB teachers in Jombang was at a moderate level, and their work stress was in the low category. Mental workload is one of the factors that can cause work stress on SLB teachers in Jombang.Keywords: mental workload, SLB teachers, work stress